ANALISIS PENGUNGKAPAN INFORMASI LINGKUNGAN DALAM LAPORAN KEUANGAN PDAM KABUPATEN BONDOWOSO : PERSPEKTIF GREEN ECONOMI DAN TANGGUNGJAWAB SOSIAL PERUSAHAAN: ANALISIS PENGUNGKAPAN INFORMASI LINGKUNGAN DALAM LAPORAN KEUANGAN PDAM KABUPATEN BONDOWOSO : PERSPEKTIF GREEN ECONOMI DAN TANGGUNGJAWAB SOSIAL PERUSAHAAN - Prayogi, Gusti Dian; Widiar Onny Kurniawan (Universitas PGRI Adi Buana, 2024)
This research aims to analyze the disclosure of environmental information in the financial statements of the Regional Drinking Water Company (PDAM) of Bondowoso Regency, considering the perspectives of green economy and corporate social responsibility. The disclosure of environmental information is increasingly important in the context of environmental protection and business sustainability. A qualitative approach is used to analyze the financial statements of PDAM Bondowoso Regency with a focus on environmental information disclosure elements. Findings from this research are expected to provide new insights into environmental information disclosure practices in the public sector, especially in regional companies such as PDAM. The implications of this analysis can contribute to the development of green economy and corporate social responsibility in Bondowoso Regency and encourage other companies to improve transparency and accountability in disclosing environmental information in the financial statements of PDAM Bondowoso Regency. In conclusion, the management of waste by PDAM Bondowoso Regency still has shortcomings, such as suboptimal waste treatment, gaps in handling various types of waste, technological limitations, and lack of awareness or understanding. The disclosure of environmental information in financial statements is also constrained by factors such as lack of awareness, resource constraints, and regulatory uncertainty. This results in suboptimal disclosure of prevention and detection cost allocations and environmental failure costs. Steps are needed to enhance transparency, such as improvements in disclosing cost allocations and detailed operating costs for waste management. Thus, stakeholders can better understand PDAM's efforts to maintain environmental sustainability and public health